Flexible electrode plate with large-aperture channel and high specific surface area and preparation method thereof

By preparing COF-5/Ti3C2Tx composite electrode sheets with large pore diameter channels and high specific surface area, the challenges of zinc ion hybrid capacitors in terms of cycle life and electrochemical performance are solved, and the low-cost preparation of high-capacity and long-life high-performance zinc ion hybrid capacitors are achieved.

CN119764068APending Publication Date: 2025-04-04ZHEJIANG SCI-TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411905311.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

There are challenges in terms of cycle life and electrochemical performance of zinc ion hybrid capacitors, including the formation of zinc dendrites, irreversible dissolution and passivation of zinc, and the electrochemical performance of flexible electrode sheets needs to be improved.

Method used

Using a flexible electrode sheet preparation method with large pore diameter channels and high specific surface area, a thin film is formed by vacuum filtration of the Ti3C2Tx small-layer dispersion liquid, and an electrode sheet is obtained after vacuum drying. Then, COF-5 is grown in situ in the precursor solution containing 1,4-phenyldiboric acid and 2,3,6,7,10,11-hexahydroxytriphenyl to form a COF-5/Ti3C2Tx composite electrode sheet.

Benefits of technology

The low-cost preparation of high-performance zinc ion hybrid capacitors with high capacity and long life is achieved, and the obtained flexible electrode sheets show excellent electrochemical performance in the zinc ion hybrid capacitor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764068A_ABST
    Figure CN119764068A_ABST
Patent Text Reader

Abstract

The invention provides a flexible electrode plate with a large-aperture channel and a high specific surface area and a preparation method of the flexible electrode plate. The preparation method disclosed by the invention comprises the following steps: preparing MAX into a Ti < 3 > C < 2 > T < x > few-layer dispersion liquid; the Ti3C2Tx few-layer dispersion liquid is subjected to vacuum filtration and drying to obtain a Ti3C2Tx electrode plate, the Ti3C2Tx electrode plate is placed in a solution containing a 1, 4-benzene diboronic acid precursor and a 2, 3, 6, 7, 10, 11-hexahydroxy triphenyl precursor to grow COF-5 in situ, and the flexible electrode plate with a large-aperture channel and a high specific surface area is obtained. The preparation method is simple, and the obtained flexible electrode plate shows excellent electrochemical performance when applied to the zinc ion hybrid capacitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of zinc ion hybrid capacitors, and in particular to a flexible electrode sheet with a large aperture channel and a high specific surface area and a preparation method thereof. Background Art

[0002] As a new type of energy storage device, zinc ion hybrid capacitors combine the advantages of batteries and supercapacitors, and have the characteristics of high energy density and high power density. However, its development still faces some challenges, including the formation of zinc dendrites, irreversible dissolution and passivation of zinc, which limit the cycle life of capacitors. Currently, flexible electrode sheets are widely used in the wearable field, but the electrochemical performance still needs to be improved.

[0003] Ti 3 C 2 T x Although the material exhibits excellent performance, its low capacity remains a challenge. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method and application of a flexible electrode sheet with large pore diameter channels and high specific surface area. The preparation method is simple, and the obtained flexible electrode sheet exhibits excellent electrochemical performance when applied to zinc ion hybrid capacitors.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a flexible electrode sheet with a large pore size channel and a high specific surface area, comprising the following steps:

[0007] MAX, lithium fluoride and concentrated hydrochloric acid were mixed, etched, ultrasonically stripped under inert gas protection, and deionized water was added to prepare Ti 3 C 2 T x Few-layer dispersion;

[0008] The Ti 3 C 2 T x The thin layer dispersion was vacuum filtered to obtain Ti 3 C 2 T x Thin film; Ti 3 C 2 T x The film was vacuum dried to obtain Ti 3 C 2 T x Electrode sheet;

[0009] Ti 3 C 2 Tx The electrode sheet is placed in a solution containing 1,4-phenylenediboric acid precursor and 2,3,6,7,10,11-hexahydroxytriphenyl precursor, and COF-5 is grown in situ to obtain COF-5 / Ti 3 C 2 T x Composite electrode sheet.

[0010] Preferably, the Ti 3 C 2 T x The concentration of the thin layer dispersion is 2-3 mg / ml.

[0011] The concentration of the 1,4-phenylenediboronic acid precursor solution is 1.5-3.5 mg / mL.

[0012] The concentration of the 2,3,6,7,10,11-hexahydroxytriphenylene precursor solution is 1-2 mg / mL.

[0013] Preferably, the Ti 3 C 2 T x The electrode sheet reacts in the 1,4-phenyldiboric acid precursor and 2,3,6,7,10,11-hexahydroxytriphenyl precursor solutions for 12 hours.

[0014] The sum of the mass of the 1,4-phenylenediboronic acid precursor and the 2,3,6,7,10,11-hexahydroxytriphenylene precursor in the 1,4-phenylenediboronic acid and 2,3,6,7,10,11-hexahydroxytriphenylene precursor solution and Ti 3 C 2 T x The mass ratio of the electrode sheets is (3-10):(60).

[0015] Preferably, the Ti 3 C 2 T x The method for preparing the few-layer dispersion comprises the following steps:

[0016] Mix MAX, lithium fluoride and concentrated hydrochloric acid for etching. Inert gas such as N 2 Ultrasonic peeling under protection, adding deionized water to prepare Ti 3 C 2 T x Small layer dispersion.

[0017] Preferably, the concentration of the concentrated hydrochloric acid is 6 to 10 mol / L;

[0018] The usage ratio of the MAX, lithium fluoride and concentrated hydrochloric acid is 1 g: 1 g: (12-20) mL.

[0019] Preferably, the etching is performed under stirring conditions;

[0020] The etching temperature is 35-37° C. and the etching time is 24-28 hours.

[0021] Preferably, the mixing comprises stirring and ultrasound performed sequentially;

[0022] The stirring temperature is 25-30° C., and the rotation speed is 100-300 r / min.

[0023] The present invention also provides a flexible electrode sheet with a large pore size channel and a high specific surface area prepared by the preparation method described in the above technical solution, which is COF-5 / Ti 3 C 2 T x Composite electrode sheet, the COF-5 / Ti 3 C 2 T x The composite electrode sheet includes 1,4-phenylenediboric acid and 2,3,6,7,10,11-hexahydroxytriphenyl and Ti 3 C 2 T x .

[0024] The present invention also provides the application of the flexible electrode sheet with large aperture channels and high specific surface area described in the above technical solution in the field of zinc ion hybrid capacitors.

[0025] The preparation method of the present invention is simple and can realize low-cost preparation of high-performance aqueous zinc ion hybrid capacitors with high capacity and long life, and the obtained flexible electrode sheet exhibits excellent electrochemical performance when applied to zinc ion hybrid capacitors. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 COF-5 / Ti described in Example 1 3 C 2 T x SEM image of the electrode sheet;

[0027] Figure 2 The zinc ion hybrid capacitor described in Example 1 is 0.1A g -1 GCD cycle curve under current. DETAILED DESCRIPTION

[0028] The present invention provides a method for preparing a flexible electrode sheet with a large pore size channel and a high specific surface area, comprising the following steps:

[0029] MAX, lithium fluoride and concentrated hydrochloric acid were mixed, etched, ultrasonically stripped under inert gas protection, and deionized water was added to prepare Ti 3 C 2 Tx Few-layer dispersion;

[0030] The thin layer dispersion was vacuum filtered to obtain Ti 3 C 2 T x Thin film; Ti 3 C 2 T x The film was vacuum dried to obtain Ti 3 C 2 T x Electrode sheet;

[0031] The Ti 3 C 2 T x The electrode sheet is placed in a precursor solution containing 1,4-phenylenediboric acid precursor and 2,3,6,7,10,11-hexahydroxytriphenylene, and COF-5 is grown in situ to obtain COF-5 / Ti 3 C 2 T x Composite electrode sheet.

[0032] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0033] In the present invention, the Ti 3 C 2 T x The optimal concentration of the dispersion is 2.5 to 3 mg / mL. In the present invention, the amounts of the 1,4-phenylenediboronic acid precursor and the 2,3,6,7,10,11-hexahydroxytriphenylene precursor are preferably 1.5 to 1.75 mg / mL and 1.0 to 1.25 mg / mL, respectively;

[0034] In the present invention, the Ti 3 C 2 T x The reaction time of the electrode sheet in the 1,4-phenylenediboric acid precursor and 2,3,6,7,10,11-hexahydroxytriphenyl precursor solution is preferably 12 to 14 hours.

[0035] In the present invention, the Ti 3 C 2 T x The method for preparing the few-layer dispersion preferably comprises the following steps:

[0036] Mix MAX, lithium fluoride and concentrated hydrochloric acid for etching. 2 Ultrasonic peeling under protection, adding deionized water to prepare Ti 3 C 2 T x Small layer dispersion.

[0037] In the present invention, the MAX is preferably Ti 3 AlC 2 .

[0038] In the present invention, the concentration of the concentrated hydrochloric acid is preferably 6 to 10 mol / L, more preferably 7 to 9 mol / L, and most preferably 7.5 to 8.5 mol / L.

[0039] In the present invention, the usage ratio of MAX, lithium fluoride and concentrated hydrochloric acid is preferably 1 g: 1 g: (12-20) mL, more preferably 1 g: 1 g: (13-18) mL, and most preferably 1 g: 1 g: (14-16) mL.

[0040] In the present invention, the etching is preferably carried out under stirring conditions; the etching temperature is preferably 35-36° C.; and the etching time is preferably 24-25 hours. The present invention does not have any special limitation on the stirring speed, and any speed known to those skilled in the art can be used.

[0041] After the etching is completed, the present invention also preferably includes centrifugal washing of the obtained precipitate; the rotation speed of the centrifugal washing is preferably 3500-6500 r / min, more preferably 4000-6000 r / min, and most preferably 4500-5500 r / min; the time of each centrifugal washing is preferably 3-8 min, more preferably 5-6 min. The present invention does not have any special limitation on the number of centrifugal washings, and the number of times well known to those skilled in the art can be used to make the supernatant obtained by the centrifugal washing reach pH=6-7.

[0042] In the present invention, the Ti 3 C 2 T x The preparation process is preferably carried out in a fume hood.

[0043] In the present invention, the precursors (1,4-phenylenediboronic acid and 2,3,6,7,10,11-hexahydroxytriphenyl) in the 1,4-phenylenediboronic acid and 2,3,6,7,10,11-hexahydroxytriphenyl) precursor solution are mixed with Ti 3 C 2 T x The mass ratio of the electrode sheets is (3-10):(60).

[0044] In the present invention, the mixing preferably includes stirring and ultrasound performed in sequence; in the present invention, the stirring temperature is preferably 25-30°C, more preferably 28-32°C; the rotation speed is preferably 100-300r / min, more preferably 150-250r / min, most preferably 180-220r / min; the time is preferably 30min. The present invention does not have any special limitation on the ultrasound process, and the process well known to those skilled in the art can be used.

[0045] The present invention also provides the COF-5 / Ti 3 C 2 T x Application of composite electrode sheet in the field of zinc ion hybrid capacitors The present invention does not have any special limitation on the application method, and the application method can be carried out by methods well known to those skilled in the art.

[0046] The COF-5 / Ti provided by the present invention is described below in conjunction with the embodiments. 3 C 2 T x The flexible electrode sheet with large pore size channels and high specific surface area and its preparation method and application are described in detail, but they should not be understood as limiting the scope of protection of the present invention.

[0047] Example 1

[0048] Add 1 g of lithium fluoride to 20 mL of 9 mol / L concentrated hydrochloric acid, and react at 0-4°C for 10 min to obtain a mixed solution;

[0049] 1g Ti 3 AlC 2 The powder was added to the mixture at a rate of 0.5 g / min, stirred at 35°C for 24 h, and the obtained precipitate was repeatedly centrifuged and washed with deionized water. The speed of the centrifugal washing was 3500 r / min, and the time of each centrifugal washing was 5 min. When the pH value of the supernatant reached 6.5, the supernatant was poured out, and the lower layer of colloid was taken to obtain Ti 3 C 2 T x The obtained Ti 3 C 2 T x The gel was dispersed in a certain amount of water and ultrasonically stripped for 30 min under the condition of argon gas. After centrifugation at 3500 r / min, the upper Ti 3 C 2 T x The solid content of the above dispersion was measured to be 2-5 mg / mL, and Ti 3 C 2 T x Few-layer dispersion;

[0050] The above obtained Ti 3 C 2 T x The Ti 3 C 2 T x The film was dried under vacuum at 60 °C for 8 h to obtain dry Ti 3 C 2 T x Electrode sheet.

[0051] The Ti 3 C 2 T x The electrode sheet was placed in a solution containing 1,4-phenylenediboronic acid (1.5 mg / mL) precursor and 2,3,6,7,10,11-hexahydroxytriphenyl (1.0 mg / mL) precursor and reacted at 90°C for 14 h. 3 C 2 T x Composite electrode sheet. See attached SEM picture Figure 1 .

[0052] The composite COF-5 / Ti 3 C 2 T x The electrode sheet can be used in the field of zinc ion hybrid capacitors. Cut the electrode sheet to assemble zinc ion hybrid capacitor button cells, using 2 mol ZnSO 4 The aqueous solution is the electrolyte. The prepared battery was placed in the Xinwei CT-4008Tn battery test channel for testing, and the test current was 0.1 mA cm -2 The voltage range is 0.1-1.2V, and the zinc ion hybrid capacitor is 0.1-2.0mA cm -2 The GCD cycle curve under current is shown in the attached figure. Figure 2 As shown, at 0.1 mA cm -2 After 5000 cycles at a current density of 1.37 W, the reversible capacity remained at 940 mF cm -2 .

[0053] Example 2

[0054] Add 1 g of lithium fluoride to 20 mL of 9 mol / L concentrated hydrochloric acid, and react at 0-4°C for 10 min to obtain a mixed solution;

[0055] 1g Ti 3 AlC 2The powder was added to the mixture at a rate of 0.5 g / min, stirred at 35°C for 24 h, and the obtained precipitate was repeatedly centrifuged and washed with deionized water. The speed of the centrifugal washing was 3500 r / min, and the time of each centrifugal washing was 5 min. When the pH value of the supernatant reached 6.5, the supernatant was poured out, and the lower layer of colloid was taken to obtain Ti 3 C 2 T x The obtained Ti 3 C 2 T x The gel was dispersed in a certain amount of water and ultrasonically stripped for 30 min under the condition of argon gas. After centrifugation at 3500 r / min, the upper Ti 3 C 2 T x The solid content of the above dispersion was measured to be 2-5 mg / mL, and Ti 3 C 2 T x Few-layer dispersion;

[0056] The above obtained Ti 3 C 2 T x The Ti 3 C 2 T x The film was dried under vacuum at 60 °C for 8 h to obtain dry Ti 3 C 2 T x Electrode sheet.

[0057] The Ti 3 C 2 T x The electrode sheet was placed in a solution containing 1,4-phenylenediboronic acid (1.5 mg / mL) precursor and 2,3,6,7,10,11-hexahydroxytriphenyl (1.0 mg / mL) precursor and reacted at 90°C for 18 h. 3 C 2 T x Composite electrode sheet.

[0058] Example 3

[0059] Add 1 g of lithium fluoride to 20 mL of 9 mol / L concentrated hydrochloric acid, and react at 0-4°C for 10 min to obtain a mixed solution;

[0060] 1g Ti 3 AlC 2The powder was added to the mixture at a rate of 0.5 g / min, stirred at 35°C for 24 h, and the obtained precipitate was repeatedly centrifuged and washed with deionized water. The speed of the centrifugal washing was 3500 r / min, and the time of each centrifugal washing was 5 min. When the pH value of the supernatant reached 6.5, the supernatant was poured out, and the lower layer of colloid was taken to obtain Ti 3 C 2 T x The obtained Ti 3 C 2 T x The gel was dispersed in a certain amount of water and ultrasonically stripped for 30 min under the condition of argon gas. After centrifugation at 3500 r / min, the upper Ti 3 C 2 T x The solid content of the above dispersion was measured to be 2-5 mg / mL, and Ti 3 C 2 T x Few-layer dispersion;

[0061] The above obtained Ti 3 C 2 T x The Ti 3 C 2 T x The film was dried under vacuum at 60 °C for 8 h to obtain dry Ti 3 C 2 T x Electrode sheet.

[0062] The Ti 3 C 2 T x The electrode sheet was placed in a solution containing 1,4-phenylenediboronic acid (1.5 mg / mL) precursor and 2,3,6,7,10,11-hexahydroxytriphenyl (1.0 mg / mL) precursor and reacted at 90°C for 20 h. 3 C 2 T x Composite electrode sheet.

[0063] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a flexible electrode sheet with large pore size channels and high specific surface area, characterized in that: The following steps are involved: MAX, lithium fluoride and concentrated hydrochloric acid were mixed, etched, ultrasonically stripped under inert gas protection, and deionized water was added to prepare Ti3C2T x Few-layer dispersion; The Ti3C2T x The thin layer dispersion was vacuum filtered to obtain Ti3C2T x Thin film; Ti3C2T x The film was vacuum dried to obtain Ti3C2T x Electrode sheet; Ti3C2T x The electrode sheet was placed in a solution containing 1,4-phenylenediboric acid precursor and 2,3,6,7,10,11-hexahydroxytriphenyl precursor, and COF-5 was grown in situ to obtain COF-5 / Ti3C2T x Composite electrode sheet.

2. The preparation method according to claim 1, characterized in that The concentration of the 1,4-phenylenediboric acid precursor solution is 1.5-3.5 mg / mL, and the concentration of the 2,3,6,7,10,11-hexahydroxytriphenyl precursor solution is 1-2 mg / mL; the Ti3C2T x The concentration of the thin layer dispersion is 2-3 mg / ml.

3. The preparation method according to claim 2, characterized in that: The sum of the mass of the 1,4-phenylenediboric acid precursor and the 2,3,6,7,10,11-hexahydroxytriphenylene precursor in the 1,4-phenylenediboric acid precursor and the 2,3,6,7,10,11-hexahydroxytriphenylene precursor solution is equal to the mass of the Ti3C2T x The mass ratio of the electrode sheets is (3-10):(60).

4. The preparation method according to claim 1, characterized in that: The concentration of the concentrated hydrochloric acid is 6-10 mol / L; the usage ratio of the MAX, lithium fluoride and concentrated hydrochloric acid is 1 g: 1 g: (12-20) mL.

5. The preparation method according to claim 1, characterized in that: The etching is performed under stirring conditions; The etching temperature is 35-37° C. and the etching time is 24-28 hours.

6. The preparation method according to claim 1, characterized in that: The mixing includes stirring and ultrasound performed sequentially; The stirring temperature is 25-30° C., and the rotation speed is 100-300 r / min.

7. Flexible electrode sheet with large aperture channels and high specific surface area, characterized by It is COF-5 / Ti3C2T prepared by the preparation method according to any one of claims 1 to 7. x Composite electrode sheet, the COF-5 / Ti3C2T x The composite electrode sheet includes 1,4-phenylenediboric acid, 2,3,6,7,10,11-hexahydroxytriphenyl and Ti3C2T x .